2023
DOI: 10.1109/access.2023.3275932
|View full text |Cite
|
Sign up to set email alerts
|

ARivaT: A Tool for Automated Generation of Riva-Based Business Process Architecture Diagrams

Abstract: The Riva approach is used to develop an object-based Business Process Architecture (BPA) that helps in capturing the full organizational strategies. However, due to the lack of effective tools that can generate Riva BPA models from available artifacts, producing such models is time consuming non-automatic process and it requires an exhaustive manual validation to ensure the development of error-free models. This paper introduces a novel and domain-independent tool titled 'ARivaT' to automatically generate Riva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Historically, the most common authentication method has been username and password combinations [12]. Nevertheless, the rise of sophisticated cyber threats has shown that relying solely on passwords is insufficient to prevent unauthorized access to user accounts [13], [14]. Two-factor authentication, or 2FA, is an extra layer of security that can be added to your online banking account.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the most common authentication method has been username and password combinations [12]. Nevertheless, the rise of sophisticated cyber threats has shown that relying solely on passwords is insufficient to prevent unauthorized access to user accounts [13], [14]. Two-factor authentication, or 2FA, is an extra layer of security that can be added to your online banking account.…”
Section: Introductionmentioning
confidence: 99%